Adherence to the current guidelines on antibiotic prescription among dental practitioners: A national survey - Hoda M. Abdellatif; Eman I. AlSagob; Mamata Hebbal; Sree Lalita Kotha; Mohammed Aldossary; Atrey J. Pai Khot; Anu Sara Varghese; Basma Yahya; Ghadah Alajlan; Lamar Alshamrani (PLoS ONE, 2025)
Background The global emergence and spread of antibiotic resistance jeopardise health-care advances and life expectancy. Following the latest antibiotic guidelines is crucial to combat this issue. Therefore, the objective of this study was to assess the knowledge regarding antibiotics prescription and investigate the evidence-based practices among dental practitioners in Saudi Arabia. Method This cross-sectional study was conducted during November 2020 to April 2021 in Saudi Arabia. A self-designed validated questionnaire comprising 27 close ended knowledge-based questions and 9 practice-based question was administered among dentists working in various settings through online generated link. A pilot study in 20 dental specialists and consultants was conducted prior to the study, to arise at sample size of 318. Reliability of the questionnaire was assessed with Cronbach’s α value of 0.85, face validity of 84%, and content validity ratio of 0.78. The knowledge and practice score were graded based on quartile derivatives. The data was analyzed using descriptive analysis, chi square analysis, correlation, and regression by IBM SPSS® Statistics for Windows, Version 28.0. Armonk, NY: IBM Corp. Results The average age of the participants was 36.3 ±  5.9 years, and their average experience was about 7.3 years. The mean knowledge score was 19.62 ±  4.28 with government employees scoring higher (20.03 ±  3.90) compared to private practitioners and academicians. Clinicians with less than five years of experience had significantly higher knowledge scores (p =  0.002). The majority of the participants, 218 (68.55%), had good practices while 100 (31.44%) participants showed poor practices. Moreover, only half of the participants could correctly identify the majority of case-based scenarios related to antibiotic prescriptions. Conclusion Dentists in Kingdom of Saudi Arabia have a good level of knowledge and practices on antibiotics prescription. However, some aspects of poor practices particularly among private sector clinicians necessitate the launching of educational campaigns, interventions and provision of latest guidelines for prudent use of antibiotics in dental practice.